A coating preparation process for improving the cavitation erosion resistance of an axial flow pump blade

CN121472757BActive Publication Date: 2026-10-09ZHEJIANG SHANSHI TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202511682562.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-11-17
Publication Date
2026-10-09
Estimated Expiration
2045-11-17

AI Technical Summary

Technical Problem

但此涂层厚度不均匀,结合强度低

Benefits of technology

高结合强度:通过表面复合织构化处理和优化喷涂参数,涂层与基体结合强度不低于80MPa,远高于传统涂层(50MPa以下),防止剥落。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121472757B_ABST
    Figure CN121472757B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of coating preparation process for improving the cavitation erosion resistance of axial flow pump blade, belong to non-variable capacity pump technical field.The process includes blade surface pretreatment, coating material preparation, plasma spraying and post-processing step.Pretreatment includes cleaning, roughening and surface composite texturing treatment, form textured surface;Coating material is WC-Co composite powder, wherein WC content 82-88wt%, Co content 12-18wt%, and add nano yttrium oxide;Plasma spraying forms WC-Co adhesive bottom layer on textured surface;Post-processing includes heat treatment and the preparation of gradient functional coating, transition layer is WC-Co and Al2O3-13wt%TiO2 Mixed material, surface layer is Al2O3-13wt%TiO2 Ceramic layer.The present application realizes the high bonding strength (not less than 80MPa), high hardness (not less than HV1300) and excellent cavitation erosion resistance of coating and matrix by optimizing material composition, process parameters and structure design, prolongs the service life of blade, process is simple, low in cost, suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of non-variable displacement pump technology, and more particularly to a coating preparation process for improving the cavitation resistance of axial flow pump blades. More specifically, this invention relates to preparing a composite coating on the surface of axial flow pump blades using plasma spraying technology to enhance their resistance to cavitation corrosion, thereby extending the service life and reliability of the blades. Axial flow pumps are widely used in water conservancy, chemical industry, energy, shipbuilding, and aerospace fields. Their blades are prone to cavitation corrosion in high-speed water flow, leading to material loss, reduced efficiency, and frequent maintenance. This invention solves the problems of low coating bonding strength and insufficient cavitation resistance in existing technologies through an innovative coating process.

[0002] This invention is particularly applicable to the industrial coating treatment of large axial flow pump blades (such as blades with a diameter of more than 500 mm). Through multi-scale structural design (combining micron texture with nano reinforcement) and gradient functional material system, it achieves a breakthrough improvement in coating performance, filling the gap in existing technology for high-load and long-life application scenarios. Background Technology

[0003] Axial flow pumps are important fluid machinery, belonging to the non-variable displacement pump category. Their blades are subjected to the impact of high-speed water flow during operation, making them prone to cavitation. Cavitation occurs when a local pressure drop in the liquid causes bubble formation and collapse, generating microjet streams and shock waves that erode the material surface. This erosion leads to increased blade surface roughness, material loss, decreased efficiency, and even breakage. Statistics show that cavitation is one of the main causes of axial flow pump blade failure, resulting in significant economic losses annually.

[0004] The physical essence of cavitation erosion is the vaporization of liquid in a localized low-pressure area, forming cavitation bubbles, which subsequently collapse in a high-pressure area, generating instantaneous impact pressures and microjets up to 1 GPa. This creates cyclic impacts on the material surface, leading to fatigue spalling and accelerated corrosion. The cavitation erosion process can be divided into four stages: latent period, acceleration period, steady-state period, and decay period. In axial flow pump blades, due to uneven blade curvature and velocity distribution, cavitation erosion mostly occurs at the leading edge, trailing edge, and low-pressure side of the blades; these areas are called "cavitation-prone zones." Cavitation erosion not only leads to material loss but also causes vibration and noise, affecting the stable operation of the system.

[0005] In existing technologies, surface coating techniques are commonly used to improve the cavitation resistance of axial flow pump blades. For example, thermal spraying techniques (such as flame spraying and arc spraying) and electroplating techniques are widely used. However, these methods have several shortcomings: Low coating bonding strength: The bonding strength between traditional thermal spray coatings and the substrate is usually less than 50 MPa, and they are easily peeled off under the impact of high-speed water flow.

[0006] Poor coating density: Pores and cracks exist in the coating, allowing cavitation media to easily penetrate and accelerate corrosion.

[0007] Limited resistance to cavitation erosion: Existing coating materials (such as nickel-based alloys and ceramics) have insufficient hardness and short cavitation erosion life.

[0008] Complex processes and high costs: For example, chemical vapor deposition (CVD) requires a high-temperature environment, involves large equipment investment, and is not suitable for large blades.

[0009] Chinese patent application CN111074265A discloses a laser cladding anti-cavitation coating and its preparation method, belonging to the field of alloy coating technology. The anti-cavitation coating is a shape memory alloy coating applied to the workpiece surface via laser cladding. This shape memory alloy coating, based on its cyclic properties such as superelasticity and shape memory effect, absorbs most of the energy and pulse stress generated by cavitation impact, resulting in superelastic deformation and martensitic phase transformation. After the external force is unloaded, the shape memory alloy coating undergoes elastic recovery and reverse martensitic phase transformation, restoring its strain. This buffers and dissipates most of the energy generated by cavitation impact, preventing self-damage and achieving the goal of extending the cavitation incubation period, inhibiting the initiation and propagation of cavitation cracks, and thus improving cavitation resistance. The laser cladding process is simple and can selectively prepare coatings in localized, fine areas as needed, effectively reducing costs. However, this method requires high-energy laser equipment, resulting in high costs and a tendency to generate thermal stress cracks.

[0010] Further analysis of this technology reveals that while shape memory alloys (such as NiTi-based alloys) possess superelasticity, under high-speed cavitation impact, phase transformation cycles can lead to cumulative strain and microcrack initiation. Furthermore, the laser cladding process easily introduces porosity and incomplete fusion defects, reducing coating density. In addition, this method requires a large heat input to the substrate, which can easily cause blade deformation, making it particularly unsuitable for thin-walled or large blades.

[0011] Chinese patent application CN101024892A describes an electroplated composite coating, which uses an electroplating solution comprising a metal cation of a metal substrate to be deposited and carbon nanotubes to deposit the composite coating on a substrate. The composite coating includes a metal substrate and carbon nanotubes disposed within the substrate to improve the mechanical and tribological properties of the coating. However, this coating has uneven thickness and low bonding strength.

[0012] The main problems with electroplated composite coatings are: carbon nanotubes tend to agglomerate in the plating solution, leading to uneven distribution; the coating and substrate are mechanically bonded, with a bonding strength typically below 30 MPa; and the electroplated layer thickness is usually less than 100 μm, making it difficult to withstand long-term cavitation impact. Furthermore, the electroplating process involves toxic chemicals, resulting in poor environmental performance.

[0013] For example, Chinese patent application CN107488829A discloses a method for preparing a titanium carbonitride coating applied to steering pump blades, relating to the field of metal coating preparation technology. This invention includes the following steps: material preparation; grinding; cleaning; pre-coating; drying; and coating. This method is simple and low-cost. Within the same time frame, the titanium carbonitride coated blades are significantly better than uncoated blades. Furthermore, due to the lower coefficient of friction of the coated blades, the wear of the corresponding friction pair is also very small. In addition, the coated blades exhibit relatively lower noise and smoother operation. While it uses physical vapor deposition (PVD) to prepare the titanium nitride coating, the coating is relatively thin, making it suitable for small parts but not for large components such as axial flow pump blades.

[0014] While PVD technology can produce thin film coatings with high hardness and high bonding strength, its deposition rate is low, coating thickness is limited (typically <10 μm), and it has strict limitations on the shape and size of the workpiece, making it unsuitable for large curved workpieces such as axial flow pump blades. Furthermore, PVD equipment requires significant investment and has high process costs, hindering its widespread adoption in industrial production.

[0015] In addition to the aforementioned patented technologies, the industry has also attempted to improve the cavitation resistance of blades through methods such as welding, nitriding, and micro-arc oxidation. However, all of these methods have significant limitations: welding has a large heat-affected zone, which can easily lead to substrate deformation; nitriding layers are thin and have poor impact resistance; and micro-arc oxidation coatings are porous and have low bonding strength. Therefore, the industry has long faced a technical bottleneck in achieving a balance between high bonding strength, high hardness, and high density.

[0016] Therefore, there is an urgent need in the field for a novel coating preparation process that can achieve high bonding strength, high density, and excellent cavitation resistance, while being simple, low-cost, and suitable for industrial production. This invention effectively solves the above problems by using plasma spraying technology combined with optimized material composition and process parameters. Summary of the Invention

[0017] To address the shortcomings of existing technologies, the present invention aims to provide a coating preparation process for improving the cavitation resistance of axial flow pump blades. This process optimizes coating materials, spraying parameters, and post-treatment steps to produce a coating with high hardness, high bonding strength, and excellent cavitation resistance.

[0018] The above-mentioned objective of this invention is achieved through the following technical solutions: A coating preparation process for improving the cavitation resistance of axial flow pump blades includes the following steps: Step 1: Blade surface pretreatment, including cleaning, roughening and surface composite texturing treatment of the axial flow pump blade substrate to form a textured surface; Step 2: Preparation of coating material. The coating material is a composite powder of tungsten carbide (WC) and cobalt (Co), wherein the WC content is 82-88 wt% and the Co content is 12-18 wt%. Step 3: Plasma spraying. Plasma spraying is performed on the pretreated blade surface using a coating material to form a WC-Co bonding underlayer on the textured surface. Step 4: Post-treatment. The sprayed WC-Co bonding substrate is heat-treated, and then a transition layer and a top layer with gradually changing composition are sequentially prepared on the WC-Co bonding substrate using thermal spraying technology. The transition layer is a mixture of WC-Co and Al2O3-13wt%TiO2, and the top layer is an Al2O3-13wt%TiO2 ceramic layer.

[0019] In step 3, the parameters for plasma spraying include: power 45-55 kW, main gas argon with a flow rate of 45-55 L / min, auxiliary gas hydrogen with a flow rate of 8-12 L / min, and spraying distance 120-180 mm. The powder feed rate is 25-35 g / min, the spraying angle is 75-85°, and the moving speed of the spray gun relative to the blade surface is 150-250 mm / s. During the spraying process, the temperature of the blade substrate is controlled below 150°C through an auxiliary cooling system.

[0020] In step 4, the heat treatment temperature is 550-650℃, and the time is 1-2 hours. The heat treatment is carried out in a vacuum or inert gas protected environment, with a heating rate of 3-8℃ / min, and the furnace is cooled to below 150℃ before being removed from the furnace.

[0021] The core innovation of this invention lies in its three-pronged approach of "surface composite texturing + gradient functional coating + nano-reinforcement," which achieves high-strength bonding between the coating and the substrate and long-term resistance to cavitation erosion. The technical principles of each step are explained in detail below: In step 1, the blade surface pretreatment involves cleaning, roughening, and activation, which are routine operations. However, their combination with subsequent laser texturing has a synergistic effect. Sandblasting roughening not only increases the surface area but also introduces residual compressive stress, improving fatigue resistance; hydrochloric acid activation removes the oxide film, exposing the fresh metal surface and enhancing chemical bonding. Surface composite texturing, through laser processing, forms a micron-scale pit array and trench network in cavitation-prone areas. Its mechanisms include: mechanical interlocking effect: the coating material fills the pits and trenches, forming an "anchoring" structure that significantly improves bonding strength; stress dispersion effect: the microtexture can disperse cavitation shock waves, reducing stress concentration; and hydrodynamic effect: the trench network can guide fluid microflow, reducing the direct impact of cavitation collapse on the surface.

[0022] The WC-Co system was chosen as the coating material in step 2 based on its high hardness, high toughness, and good wettability. A WC content of 82-88 wt% ensures a coating hardness of at least HV1300, while a Co content of 12-18 wt% provides sufficient toughness to prevent brittle cracking. The addition of nano-yttrium oxide (Y₂O₃) serves several purposes: grain refinement: nanoparticles act as heterogeneous nucleation sites, inhibiting WC grain growth; enhanced toughness: Y₂O₃ pins cracks, hindering crack propagation; and improved thermal stability: Y₂O₃ has a high melting point, which can suppress high-temperature phase transformations.

[0023] Step 3, plasma spraying, employs optimized parameters. Argon is used as the main gas to provide a stable plasma arc, while hydrogen is used as an auxiliary gas to increase enthalpy and particle velocity. A spraying distance of 120-180mm ensures that particles are in a semi-molten state upon impact with the surface, forming a dense coating. A spraying angle of 75-85° avoids the "shadowing effect" and ensures coating uniformity. An auxiliary cooling system controls the substrate temperature below 150℃ to prevent thermal stress from causing substrate deformation or coating cracking.

[0024] In step 4, the post-treatment heat treatment eliminates residual stress from the spraying process, promotes elemental interdiffusion between the coating and the substrate, and enhances adhesion. The gradient functional coating is designed to alleviate the mismatch in thermal expansion coefficients between WC-Co and Al2O3-13wt%TiO2 (WC-Co: 5.5×10^-6 / ℃, Al2O3-13wt%TiO2: 7.5×10^-6 / ℃), preventing interfacial cracking. The transition layer achieves a smooth transition in performance through compositional gradient. The surface layer is prepared using supersonic plasma spraying, with particle velocities up to 800 m / s, forming a dense ceramic layer with a porosity of less than 2%.

[0025] First, surface composite texturing is not simply roughening; rather, it involves precisely machining a network of micron-sized pits and trenches using lasers. The geometric parameters (such as diameter, depth, and spacing) are optimized through computational fluid dynamics (CFD) simulations to ensure optimal fluid buffering under cavitation conditions. For example, the pit diameter design of 50-150 μm is based on the typical scale of cavitation collapse (approximately 100 μm), effectively dispersing impact energy. This targeted design has not been reported in existing technologies.

[0026] Secondly, the amount (1-3 wt%) and particle size (30-80 nm) of nano-yttrium oxide added to the coating material were rigorously verified through experiments: below this range, the enhancement effect was not significant; above this range, the particles were prone to agglomeration, which reduced performance. This invention is the first to discover that nano-Y2O3 within this specific range can form a "nanopinion" structure with WC-Co, reducing the crack propagation rate of the coating by more than 50% in cavitation erosion tests.

[0027] Third, the gradient coating is prepared using a dual powder feeder system to achieve a linear gradient in composition, rather than a simple multilayer stacking. This continuous gradient structure avoids interfacial stress concentration, ensuring that the coating does not peel off during thermal cycling tests (100 cycles from -20℃ to 200℃), while traditional multilayer coatings crack under the same conditions. This process parameter (such as the linear change in powder feed rate) is the key innovation of this invention.

[0028] Fourth, the entire process chain is highly integrated, employing controllable industrial equipment (such as CNC lasers and plasma spraying systems) from pretreatment to posttreatment, ensuring batch stability. For large blades, this invention also optimizes the spraying path and cooling strategy, for example, by using a multi-axis robot to control the spray gun trajectory, keeping the coating thickness deviation within ±5%, far exceeding industry standards (typically ±15%).

[0029] As a further technical solution of the present invention: In step 1, the roughening treatment in the pretreatment of the blade surface is sandblasting, and the abrasive used is angular steel grit or alumina grit with a particle size range of 0.4-0.8 mm. After sandblasting, the surface roughness Ra of the blade is 4.0-6.0 μm. After sandblasting, an activation step is also included, in which a 10-15% hydrochloric acid solution is used to chemically activate the roughened surface for 3-8 minutes.

[0030] The choice of angular steel grit or alumina grit for sandblasting is based on their high hardness and sharp edges, which effectively etch metal surfaces. A grit size of 0.4-0.8 mm balances roughening effect with surface damage, and Ra=4.0-6.0μm is the optimal anchoring roughness. A hydrochloric acid activation concentration of 10-15% effectively removes oxides such as Fe2O3 while avoiding over-corrosion. An activation time of 3-8 minutes ensures sufficient activation without damaging the substrate.

[0031] Furthermore, this invention, through experiments, revealed that the anisotropy of the surface morphology after sandblasting has a significant impact on the coating bonding strength. When the abrasive particle size is controlled within 0.4-0.8 mm, uniform anchoring points are formed on the surface. If the particle size is less than 0.4 mm, the roughness is insufficient (Ra < 4.0 μm), and the coating bonding strength decreases to below 60 MPa. If the particle size is greater than 0.8 mm, substrate damage is aggravated, and fatigue life is reduced. This parameter range was obtained through extensive orthogonal experimental optimization, ensuring the reliability of the process.

[0032] As a further technical solution of the present invention: In step 1, the surface composite texturing treatment step is as follows: in the easily cavitated area of ​​the axial flow pump blade substrate, a micron-level pit array is prepared by laser processing, and an interconnected microgroove network is processed between the pit arrays.

[0033] Laser processing utilizes a 1064 nm Nd:YAG laser, which offers high beam quality and a small heat-affected zone. The pit array design is based on the distribution characteristics of cavitation impact, and CFD simulations are used to determine cavitation-prone areas. A microgroove network connects the pits, creating a "micro-reservoir" effect that stores lubricating media in the early stages of cavitation, mitigating impact.

[0034] This invention also reveals that the connectivity of the microgroove network is crucial to cavitation resistance. If the grooves are isolated structures, the fluid buffering effect is limited; however, an interconnected network can create localized microflows, reducing cavitation collapse energy by more than 30%. The laser processing parameters (e.g., pulse frequency of 20kHz and scanning speed of 100mm / s) have been optimized to ensure texture accuracy while avoiding thermal damage; this combination of parameters is not disclosed in existing literature.

[0035] As a further technical solution of the present invention: the diameter of the pits in the micron-level pit array is 50-150μm, the depth is 30-80μm, and the center-to-center spacing of the pits is 1.5-3 times the diameter of the pits; the width of the microgrooves is 30-80μm and the depth is 20-60μm.

[0036] This parameter range has been optimized through extensive experimentation: when the pit diameter is <50μm, the coating filling is insufficient; when it is >150μm, the substrate strength is weakened. A depth-to-diameter ratio of 0.6-0.8 ensures anchoring effectiveness. A spacing of 1.5-3 times the diameter avoids stress overlap. The groove width and depth match the pits to form a continuous texture network.

[0037] Through finite element analysis (FEA), this invention verified the stress distribution under these texture parameters: under cavitation impact, the maximum equivalent stress decreased from 500 MPa on the untextured surface to 300 MPa on the textured surface, and the stress concentration factor decreased by 40%. Furthermore, when the pit spacing was 1.5-3 times the diameter, the interfacial shear strength between the coating and the substrate reached its peak, an innovative finding derived from interfacial mechanics model calculations.

[0038] As a further technical solution of the present invention: the composite powder of the coating material has a particle size of 20-40μm, and the composite powder contains 1-3% of nano-yttrium oxide (Y2O3) particles accounting for 1% of the total weight of the composite powder, wherein the particle size of the nano-yttrium oxide is 30-80nm.

[0039] A powder particle size of 20-40μm ensures complete melting in the plasma flame and prevents clogging of the powder feeder. The addition of 1-3% nano-yttrium oxide is based on a balance between reinforcing effect and dispersibility: <1% results in insignificant reinforcing effect; >3% leads to agglomeration and reduced coating density. A particle size of 30-80nm ensures the nano-effect is fully realized and prevents it from being dispersed by the plasma flame.

[0040] This invention reveals through transmission electron microscopy (TEM) analysis that nano-Y2O3 is mainly distributed at the grain boundaries of WC, forming a "grain boundary pinning" structure, which reduces the creep rate of the coating by 20% in nanoindentation tests. At the same time, the addition of nanoparticles increases the thermal conductivity of the coating by 15%, which helps dissipate heat during cavitation erosion. This synergistic effect has not been reported in previous studies of WC-Co coatings.

[0041] As a further technical solution of the present invention: in step 4, the gradient functional coating is prepared by a composite spraying process: the transition layer is prepared by atmospheric plasma spraying with a power of 40-50 kW; the surface layer is prepared by supersonic plasma spraying with a power of 60-80 kW.

[0042] Atmospheric plasma spraying (APS) is suitable for transition layer preparation due to its moderate particle velocity (300-400 m / s), enabling compositional gradients. Supersonic plasma spraying (SPS) is suitable for surface layers due to its high particle velocity (>800 m / s), resulting in a denser coating. Power ranges of 40-50 kW (APS) and 60-80 kW (SPS) have been optimized to ensure complete particle melting without overheating.

[0043] The power parameters are set based on thermodynamic calculations: when the APS power is below 40kW, particle melting is insufficient, and the coating porosity increases to over 5%; when the SPS power is above 80kW, the risk of substrate overheating increases. This invention uses a real-time temperature monitoring system to dynamically adjust the power, ensuring a stable process window. This dynamic control method is an additional innovation of this invention.

[0044] As a further technical solution of the present invention: In step 4, during the preparation of the transition layer, WC-Co powder and Al2O3-13wt%TiO2 powder are simultaneously conveyed through a dual powder feeder system, and the powder feeding rate ratio of the two powders is controlled to change linearly from 100:0 to 0:100, thereby achieving a continuous gradient change in composition.

[0045] The dual powder feeder system employs closed-loop control, achieving a powder feeding accuracy of ±2%. The linear variation in powder feeding rate avoids interfacial stress concentration caused by abrupt changes in composition. Gradual compositional changes allow the coefficient of thermal expansion to smoothly transition from 5.5 × 10⁻⁶ / ℃ at the bottom layer to 7.5 × 10⁻⁶ / ℃ at the top layer, significantly improving thermal shock resistance.

[0046] The linear gradient strategy was optimized through mathematical modeling: the powder feed rate varies linearly as a function of time, ensuring a consistent thickness for each layer (approximately 10 μm / layer). Experiments show that this gradient structure reduces residual stress by 50% and improves interfacial bonding strength by 15% in thermal cycling tests compared to a step gradient. This modeling method provides a new tool for the field.

[0047] As a further technical solution of the present invention: the coating thickness prepared by the process is 250-400μm, the bonding strength between the coating and the blade substrate is not less than 80MPa, and the average microhardness of the coating is not less than HV1300.

[0048] The coating thickness of 250-400μm was optimized through cavitation life simulation: <250μm resulted in insufficient wear resistance; >400μm led to increased internal stress and easy peeling. The bonding strength ≥80MPa was achieved through a synergistic effect of texturing and heat treatment, significantly higher than traditional coatings. The hardness ≥HV1300 benefited from the reinforcing effect of the WC-Co system and nano-Y2O3.

[0049] Accelerated cavitation testing (ASTM G32 standard) showed that the coating exhibited the lowest weight loss rate in the 250-400 μm thickness range, with peak lifetime achieved at a thickness of 300 μm (5 times longer than uncoated blades). The combined improvement in strength and hardness enabled the coating to achieve a service life exceeding 20,000 hours under simulated operating conditions (flow rate 15 m / s, pressure 0.5 MPa), meeting stringent industrial requirements.

[0050] As a further technical solution of the present invention: after the post-processing in step 4, a mechanical polishing step is also included to reduce the surface roughness Ra of the coating to 0.4-0.8 μm.

[0051] Mechanical polishing using diamond polishing paste, achieving a Ra value of 0.4-0.8 μm after polishing, significantly reduces fluid friction resistance and improves pump efficiency. Simultaneously, a smooth surface reduces cavitation nucleation sites and extends the cavitation erosion latency.

[0052] The polishing process parameters (e.g., polishing force 5-10N, time 3-5 minutes) were optimized to avoid over-polishing that would lead to coating thinning. Tests showed that pump efficiency increased by 3-5% after polishing, and the cavitation erosion latency was extended to 1.5 times that of the unpolished coating. This step is simple and easy to perform, yet highly effective, demonstrating the practicality of this invention.

[0053] A method for repairing axial flow pump blades as described above includes the following steps: cleaning and inspecting the cavitation area of ​​the failed blade; machining the repairable area to form a new surface to be treated; and then re-preparing the composite texture and gradient coating on the surface to be treated using the above-described process.

[0054] In the maintenance process, ultrasonic or penetrant testing is used to ensure the substrate is free of cracks. Turning removes the damaged layer, creating a fresh surface. Re-fabrication of the texture and coating can restore the blade's lifespan to over 90% of that of a new blade, significantly reducing maintenance costs.

[0055] Maintenance case studies show that blades repaired using this invention exhibit cavitation performance comparable to new blades after being put back into operation, at a cost that is only 30% of the price of new blades. This method is particularly suitable for the reuse of expensive materials (such as titanium alloy blades), demonstrating significant economic and environmental benefits.

[0056] In summary, compared with the prior art, the present invention has at least one of the following beneficial technical effects: High bonding strength: Through surface composite texturing treatment and optimized spraying parameters, the bonding strength between the coating and the substrate is no less than 80MPa, which is much higher than that of traditional coatings (below 50MPa), preventing peeling.

[0057] Excellent cavitation resistance: The gradient coating structure (WC-Co base layer, gradient transition layer, ceramic surface layer) combined with nano-yttrium oxide reinforcement results in high hardness (above HV1300), good density (porosity less than 2%), and increases cavitation erosion life by 3-5 times.

[0058] Wide process adaptability: Plasma spraying process is simple, parameters are controllable, and it is suitable for the industrial production of large blades, reducing costs by more than 30%.

[0059] Environmental friendliness and maintainability: The process is free of toxic substances and provides blade maintenance methods to extend the overall lifespan.

[0060] The inventiveness of this invention is further demonstrated by its resolution of a long-standing technical bias: it is generally believed in the art that high-hardness coatings (such as ceramics) and high-toughness coatings (such as metals) are difficult to achieve simultaneously in a single process. This invention, through gradient functional design and nano-reinforcement, breaks this bias, achieving a synergistic improvement in both hardness and toughness. Furthermore, while conventional wisdom holds that surface texture reduces substrate strength, this invention, by optimizing texture parameters, actually enhances the substrate's fatigue resistance.

[0061] This invention significantly improves the cavitation resistance of axial flow pump blades through surface composite textured design and gradient coating structure innovation. It employs laser processing to create a network of micron-level pits and grooves in the cavitation-prone areas of the blades, greatly increasing the coating bonding area. Combined with sandblasting and chemical activation treatment, the coating bonding strength is increased to no less than 80 MPa, effectively overcoming the problem of easy peeling of traditional coatings.

[0062] This process innovatively selects WC-Co composite powder and adds nano-yttrium oxide (WC content 82-88wt%, Y2O3 added 1-3wt%) in the material system. By optimizing plasma spraying parameters (power 45-55kW, precise control of gas flow and spraying distance) and subsequent heat treatment (550-650℃ vacuum protection), a dense and high-hardness WC-Co bonding underlayer (hardness ≥HV1300) is formed with a porosity of less than 2%, which significantly improves the density and impact resistance of the coating.

[0063] Furthermore, this invention achieves a transition layer with continuously varying composition (WC-Co and Al2O3-13wt%TiO2 gradient mixing) and a surface layer (Al2O3-13wt%TiO2) by supersonic plasma spraying through a dual powder feeder system, which effectively alleviates interlayer thermal stress and enables the coating to achieve a lifespan 3-5 times that of uncoated blades in cavitation erosion experiments, thus solving the industry problem of easy cracking or insufficient adhesion of single-material coatings.

[0064] As is well known to those skilled in the art, the mechanism of cavitation damage involves multi-physics coupling effects, including hydrodynamics, material fatigue, and chemical corrosion. Traditional coating technologies often focus on optimizing a single performance, such as increasing hardness or toughness, but neglect the interfacial compatibility between the coating and the substrate, thermal stress matching, and performance stability under long-term service. For example, although WC-Co coatings have high hardness, they are prone to cracking when directly sprayed onto steel substrates due to differences in thermal expansion coefficients; ceramic coatings have good resistance to cavitation erosion, but their bonding strength is low. This invention, through systematic process innovation, integrates surface texturing, nano-reinforcement, and gradient coating structures into a single process for the first time, solving the aforementioned synergistic challenges.

[0065] Furthermore, existing technologies lack specific solutions for large blades (such as ship propeller blades exceeding 1 meter in length). Large blades are prone to deformation due to heat accumulation during the spraying process, and the uniformity of the coating is difficult to control. This invention achieves stable processing of large workpieces by optimizing the cooling system and spraying path, which has not been reported in previous literature.

[0066] From an economic perspective, downtime and maintenance costs due to cavitation account for more than 40% of the pump's lifecycle cost. This invention significantly reduces the total lifecycle cost by extending blade life by 3-5 times, a benefit that has not been adequately recognized in existing technologies. Attached Figure Description

[0067] Figure 1 This is a flowchart of the present invention. Detailed Implementation

[0068] The technical solutions in the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of this application without creative effort are within the scope of protection of this application.

[0069] In the description of this application, it should be noted that the terms "upper," "lower," "inner," "outer," "top / bottom," etc., indicating the orientation or positional relationship are based on the orientation or positional relationship shown in the accompanying drawings, and are only for the convenience of describing this application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation of this application. Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance.

[0070] In the description of this application, it should be noted that, unless otherwise expressly specified and limited, the terms "installed," "equipped with," "sleeved / connected," "connected," etc., should be interpreted broadly. For example, "connection" can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium; it can be a connection within two components. Those skilled in the art can understand the specific meaning of the above terms in this application based on the specific circumstances.

[0071] To better illustrate the technical effects of the present invention, a detailed description is provided below with reference to specific embodiments and comparative examples. All embodiments were conducted under the same testing standards to ensure data comparability. Example 1

[0072] Reference Figure 1 The present invention discloses a coating preparation process for improving the cavitation resistance of axial flow pump blades, comprising the following steps: Step 1: Blade Surface Pretreatment: The axial flow pump blade substrate (usually stainless steel or titanium alloy) undergoes cleaning, roughening, and surface composite texturing treatment sequentially. Cleaning is performed using ultrasonic cleaning with organic solvents (such as acetone) to remove oil stains. Roughening is achieved through sandblasting using angular steel grit or alumina grit (0.4-0.8 mm particle size) to achieve a surface roughness Ra of 4.0-6.0 μm, followed by activation with a 10-15% hydrochloric acid solution for 3-8 minutes to enhance surface activity. Surface composite texturing treatment involves laser processing to create a micron-level pit array (pit diameter 50-150 μm, depth 30-80 μm, spacing 1.5-3 times the diameter) and a microgroove network (width 30-80 μm, depth 20-60 μm) in cavitation-prone areas, forming a textured surface that improves coating adhesion and cavitation resistance.

[0073] In the cleaning process, ultrasonic cleaning with acetone for 30 minutes thoroughly removes grease and adsorbed impurities. Sandblasting pressure is 0.6 MPa, angle is 90°, and moving speed is 5 mm / s to ensure uniform roughening. After hydrochloric acid activation, rinsing with deionized water and drying are necessary to avoid chloride ion residue. Laser texturing is performed using a CNC platform with a positioning accuracy of ±5 μm. The texturing area is determined based on CFD analysis and typically occupies 20-40% of the blade surface area.

[0074] Step 2, Coating Material Preparation: The coating material is WC-Co composite powder with a WC content of 82-88 wt%, a Co content of 12-18 wt%, and a powder particle size of 20-40 μm. In addition, 1-3 wt% nano-yttrium oxide (Y2O3, particle size 30-80 nm) is added as a reinforcing phase to improve the coating's toughness and thermal stability.

[0075] The WC-Co composite powder was prepared by atomization, and then mixed with nano-Y2O3 by high-energy ball milling for 2 hours at 300 rpm to ensure uniform dispersion. The powder needs to be dried at 80℃ for 2 hours before use to prevent agglomeration.

[0076] Step 3, Plasma Spraying: The above-mentioned coating material is applied to the pretreated blade surface using plasma spraying. Parameters include: power 45-55 kW, argon flow rate 45-55 L / min, hydrogen flow rate 8-12 L / min, spraying distance 120-180 mm, powder feed rate 25-35 g / min, spraying angle 75-85°, and spray gun movement speed 150-250 mm / s. During spraying, an auxiliary cooling system is used to control the substrate temperature below 150°C to prevent thermal deformation. This process forms a WC-Co bonding underlayer with a thickness of approximately 50-100 μm.

[0077] The plasma spraying equipment is a Sulzer Metco F4 model, with a dual-disc powder feeder and a powder feeding accuracy of ±1 g / min. The cooling system uses compressed air injection, and a temperature sensor monitors the substrate temperature in real time.

[0078] Step 4, Post-treatment: The WC-Co bonding underlayer is heat-treated (550-650℃, 1-2 hours, vacuum or inert protection) to eliminate internal stress. Then, a gradient functional coating is prepared using thermal spraying technology: the transition layer is a mixture of WC-Co and Al2O3-13wt%TiO2, with the powder feeding rate ratio linearly changing from 100:0 to 0:100 through a dual powder feeder system to achieve a gradual change in composition, using atmospheric plasma spraying (power 40-50 kW); the top layer is an Al2O3-13wt%TiO2 ceramic layer, using supersonic plasma spraying (power 60-80 kW). Finally, mechanical polishing is performed to reduce the surface roughness Ra to 0.4-0.8 μm. The final coating has a total thickness of 250-400 μm, a bonding strength of not less than 80 MPa, and an average microhardness of not less than HV1300.

[0079] Heat treatment was carried out in a vacuum furnace with a vacuum level ≤10^-3 Pa and a heating rate of 5℃ / min, followed by furnace cooling. In the gradient coating preparation, the transition layer thickness was 100-150 μm, and the surface layer thickness was 100-150 μm. Polishing was performed using a CNC polishing machine with a polishing force of 5-10 N and a polishing time of 3-5 minutes.

[0080] This embodiment also includes a method for repairing axial flow pump blades as described above, comprising the following steps: cleaning and inspecting the cavitation area of ​​the failed blade; machining the repairable area to form a new surface to be treated; and then re-preparing the composite texture and gradient coating on the surface to be treated using the above-described process.

[0081] Before implementing this invention, the relevant testing standards need to be defined: Bond strength test: The bond strength between the coating and the substrate was measured using the tensile method according to ASTM C633 standard. The specimen size was φ25mm×10mm, bonded with epoxy resin, and loaded at a rate of 1mm / min on a universal testing machine until failure.

[0082] Microhardness test: According to ASTM E384 standard, a Vickers hardness tester (load 300g, holding time 15s) was used to take the average value of 5 points on the coating cross section to avoid the influence of porosity.

[0083] Cavitation performance test: According to the ASTM G32 vibration cavitation standard, the sample is immersed in deionized water, the amplitude rod frequency is 20kHz, the amplitude is 50μm, the test time is 0~20 hours, and the weight is weighed every 2 hours (accuracy 0.1mg) to calculate the cumulative weight loss.

[0084] Porosity analysis: According to ASTM B276, metallographic image analysis software (such as ImageJ) was used to photograph the coating cross section and calculate the porosity area ratio.

[0085] Microstructure characterization: Scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS) were used to observe the coating morphology, elemental distribution and interfacial bonding.

[0086] Taking a certain type of axial flow pump with stainless steel blades (material is 304 stainless steel) as an example, the process of this invention is implemented.

[0087] Experimental materials and equipment: Base: 304 stainless steel axial flow pump blades (dimensions 200mm×150mm×10mm).

[0088] Coating material: WC-Co composite powder (WC content 85wt%, Co content 15wt%, particle size 30μm, supplier is HCStarck).

[0089] Equipment: Ultrasonic cleaning machine (frequency 40kHz), sandblasting machine (pressure 0.6MPa), laser processing system (wavelength 1064nm), atmospheric plasma spraying system (Sulzer Metco F4 type), supersonic plasma spraying system (GP-80 type).

[0090] Step 1: Blade surface pretreatment Cleaning: Immerse the leaves in acetone and ultrasonically clean for 30 minutes to remove oil and impurities.

[0091] Roughening treatment: A sandblasting machine is used with alumina sand (0.5mm particle size), sandblasting pressure of 0.6MPa, angle of 90°, and moving speed of 5mm / s to achieve a surface roughness Ra of 5.0μm.

[0092] Activation: Then activate with 12% hydrochloric acid solution for 5 minutes, rinse with water and dry.

[0093] Surface composite texturing treatment: Using a laser processing system (wavelength 1064nm), an array of pits (diameter 100μm, depth 50μm, spacing 200μm) and a microgroove network (width 50μm, depth 40μm) are processed in the cavitation-prone area of ​​the blade leading edge (accounting for 30% of the surface area) to form a textured surface with a texture density of 40% (pit coverage).

[0094] Laser parameters: pulse frequency 20 kHz, scanning speed 100 mm / s, power 30 W. The textured surface morphology was inspected using a white light interferometer; pit depth deviation ±5 μm, groove width deviation ±3 μm.

[0095] Step 2: Preparation of Coating Materials WC-Co composite powder: WC content 85wt%, Co content 15wt%, powder dried at 80℃ for 2 hours, sieved before feeding, particle size 30μm, mechanically mixed evenly.

[0096] The nano-Y2O3 was added at a concentration of 2 wt%, and uniform dispersion was achieved by ball mixing for 2 hours. The powder flowability test met the ASTM B213 standard, with a flow time of <25 s / 50g.

[0097] Step 3: Plasma spraying Parameters: Power 50kW, argon flow rate 50 L / min, hydrogen flow rate 10 L / min, spraying distance 150mm, powder feed rate 30g / min, spraying angle 80°, spray gun movement speed 200mm / s. An auxiliary cooling system maintains the substrate temperature at 120℃. A WC-Co bonding underlayer is formed after spraying, with a thickness of 80μm.

[0098] After spraying, the coating surface is silver-gray with no visible cracks. Metallographic testing shows that the coating thickness uniformity deviation is ±10μm.

[0099] Step 4: Post-processing Heat treatment: Under argon protection, the temperature is increased to 600℃ at 5℃ / min, held for 1.5 hours, and then cooled with the furnace.

[0100] Gradient coating preparation: The transition layer was prepared by atmospheric plasma spraying (power 45 kW), and the powder feeding rate ratio of WC-Co and Al2O3-13wt%TiO2 powder was gradually changed from 100:0 to 0:100 by dual powder feeders, with a thickness of 100 μm; the surface layer was prepared by supersonic plasma spraying (power 70 kW) to form an Al2O3-13wt%TiO2 ceramic layer with a thickness of 120 μm.

[0101] Mechanical polishing: Using diamond polishing paste, the surface roughness Ra is reduced to 0.6 μm.

[0102] After polishing, the coating surface has a uniform gloss and no orange peel effect. The Ra value was measured to be 0.6 ± 0.1 μm using a profilometer.

[0103] The performance test results are shown in Table 1: Table 1. Coating performance data of Example 1 and comparative examples Bond strength (MPa) 85 40 ASTM C633 Microhardness (HV) 1350 800 ASTM E384 Cavitation weight loss (20h, mg) 15 50 ASTM G32 Porosity (%) 1.8 5.5 ASTM B276 Coating thickness (μm) 300 150 Cross-section measurement In summary, the total coating thickness is 300 μm, with a bonding strength of 85 MPa (ASTM C633) and a microhardness of HV1350 (ASTM E384). Cavitation erosion testing (ASTM G32, 20 hours): cumulative weight loss is 15 mg, 25% of that of the uncoated blade (60 mg), resulting in a 4-fold increase in lifespan. Porosity is 1.8% (image analysis), and SEM shows a dense coating with no interface cracks. In comparison, traditional arc-sprayed Ni-based coatings (comparative example) exhibit a bonding strength of 40 MPa, a hardness of HV800, and a cavitation erosion weight loss of 50 mg.

[0104] SEM analysis revealed an interdiffusion zone of approximately 2 μm wide at the interface between the WC-Co bonding substrate and the matrix, confirming metallurgical bonding. The transition layer exhibited a continuous compositional gradient with no obvious interface. The surface layer displayed a typical layered structure with low porosity.

[0105] To further verify the universality of the invention, Example 1 also tested the effects on different substrate materials (such as titanium alloy TC4). The results showed that the coating bonding strength remained above 82 MPa and the hardness was HV1320, indicating that the invention is applicable to a variety of blade materials.

[0106] Long-term durability test: The coated blades were subjected to simulated operating conditions (flow rate 15 m / s, temperature 50 °C) for 5000 hours. Subsequent testing showed no coating peeling and a weight loss of only 5 mg, far lower than the comparative example (30 mg). This data supports the long-term reliability of the present invention. Example 2

[0107] A coating preparation process for improving the cavitation erosion resistance of axial flow pump blades differs from Example 1 in that: the coating material contains 83wt% WC, 15wt% Co, and 2wt% nano-yttrium oxide (particle size 50nm, uniformly dispersed by mechanical ball mixing for 2 hours); the plasma spraying power is 55kW; and the heat treatment temperature is 650℃. Results: The coating thickness is 280μm, the bonding strength is 88MPa, the hardness is HV1400, and the cavitation erosion lifetime is increased by 4.5 times.

[0108] In this embodiment, the WC content was slightly lower, the Co content remained unchanged, and 2% Y₂O₃ was added, which further improved the coating toughness, slightly increased the hardness, and enhanced the bonding strength to 88 MPa. The cavitation weight loss was 14 mg, and the lifetime was extended by 4.5 times. Microscopic analysis showed that under these parameters, the nano-Y₂O₃ was more uniformly distributed, and the coating fracture toughness (KIC) reached 12 MPa·m⁻¹ / ², which is 10% higher than in Example 1. Example 3

[0109] A coating preparation process for improving the cavitation erosion resistance of axial flow pump blades differs from Example 1 in that: the coating material contains 88wt% WC, 11wt% Co, and 1wt% nano-yttrium oxide (particle size 50nm, uniformly dispersed by mechanical ball mixing for 2 hours); the plasma spraying power is 52kW; and the heat treatment temperature is 640℃. Results: The coating thickness is 285μm, the bonding strength is 90MPa, the hardness is HV1380, and the cavitation erosion lifetime is increased by 4.8 times.

[0110] In this embodiment, the upper limit of WC content and the lower limit of Co content are achieved, resulting in high coating hardness and a further improvement in bonding strength to 90 MPa. The cavitation erosion weight loss is 12 mg, demonstrating optimal performance. This combination also exhibits excellent performance in high-temperature cavitation erosion tests (80°C water temperature), with a weight loss of only 18 mg, indicating that the present invention is suitable for high-temperature environments. Example 4

[0111] A coating preparation process to improve the cavitation erosion resistance of axial flow pump blades differs from Example 1 in that: the surface texture parameters are adjusted, with pit diameter of 150 μm and depth of 80 μm; and the transition layer spraying power is 50 kW. Results: The coating exhibits a bonding strength of 85 MPa and excellent cavitation erosion resistance.

[0112] In this embodiment, the pit diameter and depth are increased while the texture density remains unchanged and the bonding strength is maintained at 85 MPa. However, the cavitation weight loss is reduced to 10 mg, indicating that larger textures are more conducive to cavitation resistance. CFD simulations show that larger pits can generate more stable eddies, improving the energy dispersion efficiency of cavitation collapse by 20%.

[0113] Comparative example: Using a conventional arc-sprayed nickel-based coating, the bonding strength is 40MPa, the hardness is HV800, and the cavitation erosion life is only 1 / 3 of that of the embodiment of the present invention.

[0114] Table 2: Comparison of key parameters and performance of different embodiments Example 1 85 100 85 1350 15 Example 2 83 100 88 1400 14 Example 3 88 100 90 1380 12 Example 4 85 150 85 1360 10 Comparative Example / / 40 800 50 Referring to Table 2, tests conducted through multiple embodiments showed that the coating of this invention has an average bonding strength of 82-90 MPa, a hardness of HV1300-1400, and a cavitation erosion life extended by 3-5 times, with good process stability. This invention's process has been applied in small-batch production, reducing costs by 35% and extending blade life from 1 year to 4 years. It is suitable for applications such as hydraulic pumping stations and ship propulsion systems.

[0115] Industrial application examples: A water conservancy pumping station using the coated blades of this invention found that after two years of operation, the coating remained intact with no signs of cavitation, and the pump efficiency remained at 98% of its initial value. Uncoated blades, operating under the same conditions, developed cavitation pits after only six months, resulting in a 15% decrease in pump efficiency. Another example is the application of this invention to ship propeller blades. After three years of service in saltwater, the coating showed no signs of corrosion, demonstrating its synergistic effect of corrosion resistance and cavitation resistance.

[0116] This invention overcomes the problems of low bonding strength (<50MPa), insufficient hardness, and easy peeling of traditional coatings, and significantly improves cavitation resistance (extending lifespan by 3-5 times). The innovation lies in: Surface composite texturing treatment: Laser fabrication of micron-scale pit arrays and trench networks to increase coating bonding area.

[0117] Coating material optimization: Adding nano-yttrium oxide to WC-Co composite powder (specific component range) improves toughness and thermal stability.

[0118] Gradient coating structure and process: Plasma spraying WC-Co bonding base layer + gradient transition layer (WC-Co mixed with Al2O3-13wt%TiO2) + ceramic top layer, with linear gradient of composition achieved by dual powder feeders.

[0119] Process parameter optimization: plasma spraying power (45-55kW), heat treatment temperature (550-650℃), etc.

[0120] This invention achieves a synergistic effect through the combination of these technical features: texturing increases mechanical interlocking, nano-yttrium oxide refines the coating structure, and gradient structure relieves stress, ultimately achieving a bonding strength ≥80MPa and a hardness ≥HV1300 (far exceeding the 38-45MPa and 640-750HV of prior art document 4). Examples show that cavitation erosion weight loss is only 15mg (compared to 50mg for traditional coatings), and lifespan is increased by 3-5 times, solving a long-standing technical bottleneck in cavitation erosion protection of axial flow pump blades and demonstrating industrial applicability.

[0121] The implementation principle of this invention is as follows: This invention relates to a coating preparation process for improving the cavitation resistance of axial flow pump blades, belonging to the field of non-variable displacement pump technology. The process includes blade surface pretreatment, coating material preparation, plasma spraying, and post-treatment steps. Pretreatment includes cleaning, roughening, and surface composite texturing treatment to form a textured surface; the coating material is WC-Co composite powder, wherein the WC content is 82-88 wt%, the Co content is 12-18 wt%, and nano-yttrium oxide is added; plasma spraying forms a WC-Co bonding underlayer on the textured surface; post-treatment includes heat treatment and the preparation of a gradient functional coating, with a transition layer being a mixture of WC-Co and Al2O3-13 wt% TiO2, and a surface layer being an Al2O3-13 wt% TiO2 ceramic layer. This invention achieves high bonding strength (not less than 80MPa), high hardness (not less than HV1300), and excellent cavitation resistance between the coating and the substrate by optimizing material composition, process parameters, and structural design, thereby extending the service life of the blades. The process is simple, low-cost, and suitable for industrial production.

[0122] The embodiments described herein are preferred embodiments of the present invention and are not intended to limit the scope of protection of the present invention. Therefore, all equivalent changes made in accordance with the structure, shape, and principle of the present invention should be covered within the scope of protection of the present invention.

Claims

1. A coating preparation process for improving the cavitation resistance of axial flow pump blades, characterized in that, Includes the following steps: Step 1: Blade surface pretreatment, including cleaning, roughening and surface composite texturing treatment of the axial flow pump blade substrate to form a textured surface; Step 2: Preparation of coating material. The coating material is a composite powder of tungsten carbide (WC) and cobalt (Co), wherein the WC content is 82-88 wt% and the Co content is 12-18 wt%. Step 3: Plasma spraying. Plasma spraying is performed on the pretreated blade surface using a coating material to form a WC-Co bonding underlayer on the textured surface. Step 4, post-treatment: The sprayed WC-Co bonding substrate is heat-treated, and then a transition layer and a top layer with gradually changing composition are sequentially prepared on the WC-Co bonding substrate using thermal spraying technology. The transition layer is a mixture of WC-Co and Al2O3-13wt%TiO2, and the top layer is an Al2O3-13wt%TiO2 ceramic layer. In step 4, during the preparation of the transition layer, WC-Co powder and Al2O3-13wt%TiO2 powder are simultaneously fed through a dual powder feeder system, and the powder feeding rate ratio of the two powders is controlled to change linearly from 100:0 to 0:100, thereby achieving a continuous gradient change in composition.

2. The coating preparation process for improving the cavitation resistance of axial flow pump blades according to claim 1, characterized in that, In step 1, the roughening treatment in the blade surface pretreatment is sandblasting, and the abrasive used is angular steel grit or alumina grit with a particle size range of 0.4-0.8 mm. After sandblasting, the surface roughness Ra of the blade is 4.0-6.0 μm. Furthermore, after sandblasting, an activation step is included, in which a 10-15% hydrochloric acid solution is used to chemically activate the roughened surface for 3-8 minutes.

3. The coating preparation process for improving the cavitation resistance of axial flow pump blades according to claim 1, characterized in that, In step 1, the surface composite texturing process involves: preparing a micron-scale pit array in the easily cavitated region of the axial flow pump blade substrate using laser processing, and fabricating an interconnected microgroove network between the pit arrays.

4. The coating preparation process for improving the cavitation resistance of axial flow pump blades according to claim 1, characterized in that, The micron-scale pit array has pits with a diameter of 50-150μm and a depth of 30-80μm, and the center-to-center spacing of the pits is 1.5-3 times the pit diameter; the microgrooves have a width of 30-80μm and a depth of 20-60μm.

5. The coating preparation process for improving the cavitation resistance of axial flow pump blades according to claim 1, characterized in that, The composite powder of the coating material has a particle size of 20-40 μm, and the composite powder contains 1-3% nano-yttrium oxide particles accounting for 1% of the total weight of the composite powder, wherein the nano-yttrium oxide particles have a particle size of 30-80 nm.

6. The coating preparation process for improving the cavitation resistance of axial flow pump blades according to claim 1, characterized in that, In step 4, the gradient functional coating is prepared using a composite spraying process: the transition layer is prepared by atmospheric plasma spraying with a power of 40-50 kW; the top layer is prepared by supersonic plasma spraying with a power of 60-80 kW.

7. The coating preparation process for improving the cavitation resistance of axial flow pump blades according to claim 1, characterized in that, The coating prepared by the process has a thickness of 250-400 μm, a bonding strength between the coating and the blade substrate of not less than 80 MPa, and an average microhardness of not less than HV1300.

8. The coating preparation process for improving the cavitation resistance of axial flow pump blades according to claim 1, characterized in that, Following the post-processing in step 4, a mechanical polishing step is also included to reduce the surface roughness Ra of the coating to 0.4-0.8 μm.

9. A method for repairing the blades of an axial flow pump as described in any one of claims 1-7, characterized in that, Includes the following steps: Clean and inspect the cavitation areas of the failed blades; The areas that can be repaired are machined to create a new surface to be treated. Subsequently, the composite texture and gradient coating are re-prepared on the surface to be treated using the process described in any one of claims 1-8.

Citation Information

Patent Citations

  • Electroplated composite coating

    CN101024892A

  • Preparation method for carbon-excessive carbon nitride titanium coating applied to steering pump vane

    CN107488829A

  • Laser cladding anti-cavitation-erosion coating and preparation method thereof

    CN111074265A

  • Process for production of ceramic nanoparticle

    CN101784484A

  • Method for spraying coating with abrasive wear resistance for high temperature ball valve

    CN106884133A